Comparative Study on Cyanide and Acid Leaching for Gold, and Silver Dissolution From Deer Trail Mine Oxide and Tailings Ore - Edgar Blanco (The Minerals, Metals and Materials Society, 2009)
At the Deer Trail Mine, interest in recovering noble metals from oxide ore and tailings oxide ore with 6.0/1.0 g/t Au and 200/140 g/t Ag respectively has led to metallurgic studies focused on finding an adequate treatment for these materials. Using cyanide leaching, the silver/gold recoveries from oxide ore and oxide tailings were 39%/95% and 36%/96%, respectively. Since these recoveries were less than spectacular for silver, it was decided to explore a non-cyanide leaching process that would extract silver and gold better. Based on previous research the possibility of using aqua regia in combination with sulfuric acid was evaluated. On a laboratory scale, variables such as mineralogical composition, concentration of reagents, dissolved oxygen, reaction time, pH and temperature were evaluated. Under optimal conditions it was possible to achieve >65% silver recovery and >85% gold recovery for both oxide ore and tailings.